Dysfunction in organizing virtual reference service - Wicaksono, Arief; Bajari, Atwar; Damayani, Ninis Agustini; Khadijah, Ute Lies Siti (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: The decline in the utilization and user satisfaction of virtual reference services in the Library in Jakarta, Indonesia, indicates organizational dysfunction. Communication can be a cause and symptom of this organizational dysfunction. Purpose: This study aims to identify the source of problems in organizing virtual reference services. Method: This research employs a qualitative case study approach. Data collection was conducted through interviews, observations, and document studies. Data analysis was performed through data coding. Findings: Interaction among service team members and with other service teams occurred frequently. In contrast, the interaction between the service team and supervisor, chief supervisor, and unit leader was infrequent. The problem that appears on the surface is the failure of the management function. Conclusion: Examining organizational issues from a communication perspective can help identify the sources of dysfunction in organizing virtual reference services. A team-based work system does not necessarily result in good performance. This occurs because the behavior of organizational members is shaped not by communication within their environment but by their activities.